GAME TECHNOLOGIES AS A TYPE OF PEDAGOGICAL TECHNOLOGIES (Academia Science Repository, 2023)
This work contains theoretical material on innovative gaming technologies for preschool children. The features of the use of interactive gaming technologies in preschool educational institutions are singled out and described.